Ethical leadership, ethical climate and unethical behaviour in institutions of higher learning - Nurul Khair, Ishak; Hasnah, Haron; Ishak, Ismail (KnE Social Sciences, 2019)
Issues related to unethical behaviour is not common nowadays; and they are also the problem of higher learning institutions. This study is conducted to find out the factors that influence the intention to perform unethical behaviour in higher learning institutions in Malaysia. This paper provides some insights into the issues of unethical behaviour, specifically the behaviour of lecturers. Ethical leadership and ethical climate are identified to be the variables that might influence the intention to perform such behaviour. It then discusses the importance of ethical leadership and ethical climate in shaping the ethical conduct in higher learning institutions.